Dealing with Legal Terminology in The Translation of Business Documents - Котева, Галина (Научни трудове, 2023)
It is commonly acknowledged that one distinctive feature of legal language is the complex and unique legal vocabulary. Legal terminology is the most prominent and noticeable linguistic feature of legal language and it is one of the major sources of difficulty in translating legal documents.When we translate a term from one language into a term from another language, we should find out if the relevant concepts associated with both terms correspond. Hence, legal translation is not automatic transfer of a concept from one language into another, but it requires thorough knowledge of the two legal systems in contact as well as a comparative analysis of the text and the terms to be translated.JEL: A20
Keywords: Терминология; Правни понятия; Паралелен текст